Lelampaq Lendong Kaoq: Comic Design to Strengthen Local Literacy - Hasbullah, Hasbullah; Lukman, Lukman; I Nyoman Yoga Sumadewa; Sasih Gunalan (Fakultas Industri Kreatif Universitas Surabaya, 2025)
A high level of reading literacy is very important for the nation's progress, however the reading literacy of students in Indonesia is still below the international average. To overcome this, the government instructed every school, including junior high schools, to allocate special time for literacy activities. One effective way is to provide interesting reading books, such as comics, which students prefer. At Mataram City Middle School, students tend to be less familiar with local folklore, so it is necessary to introduce stories such as